Teenagers in foster care: Issues, themes, and debates from and for practice and policy. Issue 3 (30th July 2019) - Shuker, Lucie; Sebba, Judy; Höjer, Ingrid
Abstract: The task of fostering adolescents is unique, requiring skills, qualities, and information that acknowledge each young person's particular needs. This editorial summarises a range of research in this special issue covering parenting styles, transitions out of care, child sexual exploitation, and the needs of LGBTQ and separated teenagers. Three themes emerging from the papers are discussed: autonomy and control; risk, resilience, and trauma; and relationships, identity, and stigma.